Природно-правові джерела формування позитивістської концепції - Сливка, С.С. (Інститут держави і права ім. В.М. Корецького НАН України, 2003)
Исследуется естественное право в период зарождения позитивизма в Европе. Используются труды известных философов И. Канта, Й. Фихте, Г.В. Гегеля и Бентама, раскрываются причины критики естественного права. Доказывается необоснованность отрицания естественного права как одного из источников
юридического позитивизма. The articles presents a study into the natural law in the period of the origination of positivism in Europe. The
reference is made to works of I. Kant, J. Fichte, G. W. F. Hegel, and J. Bentham. The reasons of criticism of natural
are presented. The negation of natural law as one of the sources of legal positivism is proved to be groundless.